(untitled) (Research, Society and Development, 2022)
This research aims to evaluate how tacit technological knowledge exchanges occur, through a social network formed by employees of the maintenance programming sector, during teleworking, in an oil and gas company from the perspective of social network analysis theory -SNA. To this end, an action-research of a qualitative participatory nature of descriptive nature was carried out, through a single case study. As main results, the SNA measures calculated in this study showed that social networks in the maintenance programming sector influence the adequacy of actors to the organization in the exchange of technological knowledge, even though its density is average, with a value of 36.6%, as well as were considered important as exchanges of knowledge about the SAP software, by all actors, even if they do not use them. Finally, communication between the actors in the network needs to be improved, as the lowest density (14.7%) and strong ties directed at actors P13 and P16 are obtained. It is concluded that the results indicate the importance of treating the relationships of social actors as a factor that is directly linked to knowledge management, in the exchange of tacit technological knowledge as a learning factor in telework.